2020
DOI: 10.3390/healthcare8030188
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Anthropometric, Biochemical, Socio-Demographic, and Dietary Habits Factors on the Health Status of Urban Corporate People in a Developing Country

Abstract: This study focused on urban corporate people and applied multinomial logistic regression (MLR) to identify the impact of anthropometric, biochemical, socio-demographic and dietary habit factors on health status. Health status is categorized into four levels: healthy, caution, affected, and emergent. A cross-sectional study, based on convenience sampling method, was conducted to select 271 employees from 18 institutions under the Grameen Bank Complex, Dhaka, Bangladesh. Biochemical measurements such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Some studies in other African cities, such as Dakar (19.2% overweight and 9.7% obese) in Senegal (2015) and Ibadan (42% among women and 14% among men) in Nigeria (2010), found slightly a lower prevalence of obesity and overweight than the current study [12,25]. We speculate that this disparity might be because of differences in dietary habits and the positioning in the different phases of the demographic, nutritional, and epidemiological transition of each country [26].…”
Section: Discussioncontrasting
confidence: 61%
“…Some studies in other African cities, such as Dakar (19.2% overweight and 9.7% obese) in Senegal (2015) and Ibadan (42% among women and 14% among men) in Nigeria (2010), found slightly a lower prevalence of obesity and overweight than the current study [12,25]. We speculate that this disparity might be because of differences in dietary habits and the positioning in the different phases of the demographic, nutritional, and epidemiological transition of each country [26].…”
Section: Discussioncontrasting
confidence: 61%
“…Increasing evidence suggests regular dietary habit is crucial for maintaining normal metabolism and improving body health for human beings confronted with a deteriorating living environment 36‐38 . However, the specific molecular mechanisms underneath still have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests regular dietary habit is crucial for maintaining normal metabolism and improving body health for human beings confronted with a deteriorating living environment. [36][37][38] However, the specific molecular mechanisms underneath still have not been fully elucidated. In this study, we attempted to uncover the hypothalamus transcriptomic responses of growing pigs induced by a TRF regime based on the pig model.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the influence of socio-demographic characteristics, such as age, gender, and education level, on health status, allowing for the customization of healthcare services and interventions based on specific demographic groups. This tailored approach ensures that resources are allocated efficiently, addressing different populations' unique needs and challenges and promoting more effective healthcare outcomes [ 45 ].…”
Section: Reviewmentioning
confidence: 99%